Monoclonal Antibodies - Rezaei, Nima (IntechOpen, 2021)
Immune-based therapies are being studied extensively in a variety of immunological conditions due to their high precision and sensitivity. Monoclonal antibody (mAb) technology is a major advancement in the treatment of several infectious diseases, malignancies, and immunological disorders. This book provides comprehensive information about technologies, characterization, and application of mAbs in the clinic and laboratory.